Effectivity of Calcium, Phosphate and Vitamin D in Dental Caries Prevention - Pratiwi Soesilawati; Yasmin Firdausi Rezkika; Naqiya Ayunnisa; Maulida Putri Syarifina; Salsabilavi Soffarina; Imanuel Jeremias Laturiuw; Padma Cahyaning Pertiwi (Denta Journal Kedokteran Gigi, 2023)
Background: Micronutrient elements are vitamins and minerals that are required in small amounts but play important roles in our body. Insufficient micronutrients can affect health including dental health. Objective: Analyzing effectiveness of micronutrients (calcium, phosphorus, and vitamin D) in preventing dental caries. Literature study: This literature study was conducted from Google Scholar, Science Direct, and Pubmed (MEDLINE).  The strategy used in literature collection is in the form of writing keywords that are used to find articles to be reviewed with a publication period between 2012 - 2020.  Discussion: Dental caries is a demineralization of an inorganic part of the tooth due to a multifactorial etiology and occurs when demineralization exceeds remineralization. The calcium and phosphorus ions level in the saliva could affect the balance between demineralization and remineralization of enamel and its deficiency can strongly influence morphology of the tooth. It has been found that calcium level significantly influences hard dental tissues defense mechanisms. On the other side, vitamin D also plays an important role to form enamel and dentin in the tooth development process because of its receptor in ameloblasts and odontoblasts. Deficiency of vitamin D can cause enamel hypoplasia which is a significant factor for early childhood caries. Conclusions: Calcium, phosphorus, and vitamin D significantly affecting the demineralization and remineralization process. The optimum concentration and level of calcium, phosphorus, and vitamin D in the body effectively increase the tooth defense mechanism and reduce the dental caries.